Measurement of Rectal Diameter and Anterior Wall Thickness by Ultrasonography in Children with Chronic Constipation - Doğan, Güzide; Keçeli, Merter; Yavuz, Sibel; Topçu, Adem; Kasırga, Erhun (Turkish Journal of Gastroenterology, 2022)
Background: Measurement of rectal diameter by ultrasonography helps the clinician in the diagnosis of chronic constipation in children for whom rectal examination cannot be performed. The aim of the study is to determine the rectal diameter and anterior wall thickness values in constipated and healthy children and to evaluate the feasibility of ultrasonography in the diagnosis of functional constipation in children who refuse digital rectal examination. Methods: One hundred forty constipated and 164 healthy children participated in the study. All patients were divided into 4 subgroups according to their ages (≤3 years [group I], 3.1-6 years [group II], 6.1-12 years [group III], and >12 years [group IV]) and were referred to the radiology department. The measurement was made from above the symphysis pubis, under the ischial spine, and at the bladder neck. Anterior wall thickness measurement was performed. The measurements were recorded according to the presence or absence of fecal mass in the rectum. Results: Constipated children with fecal mass positive group III was found to have significant difference in all of the planes in rectal diameter measurement. Rectum anterior wall thickness measurement was found to be higher in constipated patients with fecal mass (+) compared to the control. Its measurements in constipated patients in group II, group III, and group IV with no fecal mass were found to be statistically higher than the control group. Conclusion: The measurement of rectal diameter and anterior wall thickness by ultrasonography as a noninvasive method was performed in children who did not want the digital rectal examination, and it may be useful in the diagnosis of constipation. Cite this article as: Doğan G, Keçeli M, Yavuz S, Topçu A, Kasırga E. Measurement of rectal diameter and anterior wall thickness by ultrasonography in children with chronic constipation. Turk J Gastroenterol. 2022;33(12):1062-1068.